Events with an isolated lepton and missing transverse momentum and measurement of W production at HERA - Aaron, F.D.; Abramowicz, H.; Abt, I.; Adamczyk, L.; Adamus, M.; Martin, M.A.; Alexa, C.; Andreev, V.; Antonelli, S.; Antonioli, P.; Antonov, A.; Antunovic, B.; et al. (Springer, 2010)
A search for events containing an isolated electron or muon and missing trans verse momentum produced in e(+/-)p collisions is performed with the H1 and ZEUS detectors at HERA. The data were taken in the period 1994-2007 and correspond to an integrated luminosity of 0.98 fb(-1). The observed event yields are in good overall agreement with the Standard Model prediction, which is dominated by single W production. In the e(+)p data, at large hadronic transverse momentum P-T(X) > 25GeV, a total of 23 events are observed compared to a prediction of 14.0 +/- 1.9. The total single W boson production cross section is measured as 1.06 +/- 0.16 (stat.) +/- 0.07 (sys.) pb, in agreement with an Standard Model (SM) expectation of 1.26 +/- 0.19 pb.